Applying real-world data to support regulatory decision - making in the United States - M. A. Borzova; А. S. Kolbin (Izdatelstvo OKI, 2021)
The article describes the legal basis for the application of real-world data to support regulatory decision-making in the United States, as well as the possibility of implementing the relevant approaches in the legislation of the Eurasian Economic Union.